Materiality Disclosure Compliance in the 2021 Sustainability Report - Chika, Tania Martina; Meiden, Carmel (AIBPM Publisher, 2023)
The study employs a qualitative approach to analyze how provincial banks define materiality, take into account stakeholders, and pinpoint material issues.. The study is focused on nine state banks. A case study research approach using materiality assessment variables was adopted. The sampling strategy used was called targeted sampling. Data analysis techniques used include data reduction, data visualization, and inference. Landesbank defines materials as critical issues with significant impact. Customers are the most influential stakeholders. The most important material issues for organizations are related to social issues. Landesbank's materiality assessment is good, but clearly needs improvement.Â Banks with already-good materiality ratings can be kept, while provincial banks with still-poor materiality ratings can have their ratings raised.Â Keywords: Materiality, Stakeholders, Sustainability Report